Clinical comparison of three-dimensional exoscope vs. operative microscope in transforaminal lumbar interbody fusion: A retrospective case-control study - Peng, Yu-jian; Zhao, Tian-bu; Dai, Jun; Wang, Qian-liang; Zhang, Qian-zhong-yi; Cao, Jun-yin; Liu, Xiao-feng (Frontiers in Surgery, 2022)
Abstract Purpose: Here, we sought to determine the safety and feasibility of three-dimensional exoscope (3D EX). We compared data on surgery, complications, postoperative drainage, hematology, and clinical outcomes in the group that underwent transforaminal lumbar interbody fusion (TLIF) using an operative microscope (OM) relative to those treated using 3D EX. Methods: We retrospectively reviewed records on 74 patients who underwent one- or two-level TLIF from August 2019 to October 2020. Repeated measures analysis of variance was used to compare pre- and post-operative visual analogue scale (VAS) scores and oswestry disability index (ODI). We used analysis of covariance to compare pre- and post-operative erythrocyte count (RBC), hemoglobin (Hb), and hematocrit (Hct). Independent sample t-tests was used to compare postoperative drainage volume, total blood loss (TBL), visible blood loss (VBL) and hidden blood loss (HBL). Results: There were no significant differences in VAS and ODI scores between the two groups at all time points (all p >0.05). RBC and HBL did not differ significantly between the two groups (all p >0.05). There were significant differences in postoperative drainage volume,TBL, Hb, and Hct values when using 3D EX relative to OM in two-level TLIF (all p <0.05), but not for one-level TLIF (all p >0.05). The two groups differed significantly with regards to VBL when used for one- or two-level TLIF (all p <0.05). Conclusion: Our data show that 3D EX is a suitable alternative to OM in TLIF. Relative to OM, 3D EX has important strengths in reducing perioperative bleeding in two-level TLIF.